2023
DOI: 10.1002/jcb.30395
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR3 suppression through miR‐1236 inhibits proliferation and induces apoptosis in ovarian cancer via ERK1/2 and AKT signaling pathways

Abstract: Vascular endothelial growth factor receptor 3 (VEGFR3) is expressed in cancer cell lines and exerts a critical role in cancer progression. However, the signaling pathways of VEGFR3 in ovarian cancer cell proliferation remain unclear. This study aimed to demonstrate the signaling pathways of VEGFR3 through the upregulated expression of miR-1236 in ovarian cancer cells. We found that the messenger RNA and protein of VEGFR3 were expressed in the ovarian cancer cell lines, but downregulated after microRNA-1236 (mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Vascular endothelial growth factor receptors (VEGFRs) are a family of transmembrane tyrosine kinase receptors involved in signal transduction pathways to control vascular development of ovarian cancer (Babaei et al, 2023a). VEGFR3 is overexpressed in ovarian cancer cell lines promoting cell growth (Babaei et al, 2023b) and has been identified as a biomarker with potential for the diagnosis and prognosis of ovarian cancer (Klasa-Mazurkiewicz et al, 2011). Moreover, VEGF is a key mediator of angiogenesis and plays a significant role in ovarian cancer development by promoting the recruitment and proliferation of endothelial cells within the tumor (Liang et al, 2015).…”
Section: Biomarkers In Clinical Developmentmentioning
confidence: 99%
“…Vascular endothelial growth factor receptors (VEGFRs) are a family of transmembrane tyrosine kinase receptors involved in signal transduction pathways to control vascular development of ovarian cancer (Babaei et al, 2023a). VEGFR3 is overexpressed in ovarian cancer cell lines promoting cell growth (Babaei et al, 2023b) and has been identified as a biomarker with potential for the diagnosis and prognosis of ovarian cancer (Klasa-Mazurkiewicz et al, 2011). Moreover, VEGF is a key mediator of angiogenesis and plays a significant role in ovarian cancer development by promoting the recruitment and proliferation of endothelial cells within the tumor (Liang et al, 2015).…”
Section: Biomarkers In Clinical Developmentmentioning
confidence: 99%
“…miRNAs, 18–23 nucleotides in length, are a class of endogenous and noncoding RNA molecules, playing vital roles in regulating cell proliferation, differentiation, apoptosis, and other biological processes . Traditional miRNA detection methods, including northern blotting, microarray method, and RT-qPCR, are mostly extracting miRNA by lysing cells followed by extracellular detection, which generally suffer from the shortcomings of cumbersome, time-consuming, and inefficient operation, easily resulting in loss of targets during a series of operations .…”
mentioning
confidence: 99%